Rebranding Ubud as a Healing Holy Village - I Gede Sutarya (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2022)
As a center for dance and painting, Ubud village in Bali is a sought-after cultural destination for tourists. Cultural village destinations compete with other attraction centers in the global tourism market. In the 2000s, Ubud presented various healing activities, which have grown rapidly until 2022. Therefore, this study aims to analyze the rebranding of Ubud into a healing holy village. Cultural circuit and branding theories explain this based on qualitative research from 2016 to 2022. Data were collected through literature study, observation, and interviews. This has given Ubud its mythical status as a holy village for healing. Myths and meanings support the rebranding of a holy village. It was developed because of the therapeutic tourism actors that continue to investigate the uniqueness and diversity of Ubud. Furthermore, it has received support from various spiritual and healing activities. As a means of healing, Ubud’s holy village becomes a powerful brand.